2008
DOI: 10.1002/mana.200510650
|View full text |Cite
|
Sign up to set email alerts
|

Topological torsion related to some recursive sequences of integers

Abstract: For a recursively defined sequence u := (un) of integers, we describe the subgroup tu(T) of the elements x of the circle group T satisfying limn unx = 0. More attention is dedicated to the sequences satisfying a secondorder recurrence relation. In this case, we show that the size and the free-rank of tu(T) is determined by the asymptotic behaviour of the ratios qn = un u n−1 and we extend previous results of G. Larcher, C. Kraaikamp, and P. Liardet obtained from continued fraction expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Definition 6.10. [7,9] A sequence A = {a n } n in an abelian group G is called a TB-sequence is there exists a precompct group topology on G such that a n → 0.…”
Section: Precompact Group Topologies Determined By Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Definition 6.10. [7,9] A sequence A = {a n } n in an abelian group G is called a TB-sequence is there exists a precompct group topology on G such that a n → 0.…”
Section: Precompact Group Topologies Determined By Sequencesmentioning
confidence: 99%
“…The advantage of TB-sequences over the T-sequences is in the easier way of determining sufficient condition for a sequence to be a TB-sequence [7,9]. For example, a a sequence (a n ) in Z is a TB-sequence iff the subgroup t a (T) of T is infinite.…”
Section: Precompact Group Topologies Determined By Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The subgroups s u (X ) have been studied by many authors, especially in the case X = T, where X is identified with Z (see [1,6,7,10,11,15,18,24,25]). When x ∈ T is a non-torsion element, the behavior of the sequences of the form u n (x) : n ∈ ω is related to Diophantine approximation and dynamical systems (more specifically, the Sturmian flow [26]), as well as to the study of precompact group topologies with converging sequences [4,5,16].…”
Section: Introductionmentioning
confidence: 99%